Institutional legacies and governance models: A comparative study of broadband state aid in Europe - Manica, L.; Damásio, B.; Mendonça, S. (Politics & Policy, 2025)
This article explores how historical legacies and institutional configurations impact the governance models used in implementing State aid policies for broadband in France, Portugal, Spain, and the United Kingdom. The analysis is based on historical institutionalism, focusing on path dependence, critical junctures, and gradual institutional change. A comparative historical approach shows different governance models evolving due to administrative traditions and political factors. France and the United Kingdom have evolved toward decentralized models, which capitalize on institutional flexibility and strategic reforms. Conversely, Portugal and Spain face limitations from centralized structures and institutional inertia. This study elucidates the relationship between institutional structures and policy outcomes, providing policymakers with insights for addressing digital access disparities. These findings contribute to the public administration literature, emphasizing the role of timing, sequencing, and coordination in the design of effective governance frameworks and preparing for emerging challenges (such as 5G deployment) where State aid will be needed.